TRANSFORMASI NEW PUBLIC MANAGEMENT MENUJU DIGITAL GOVERNANCE: STUDI PADA SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK - Ummi Kalsum Syam; Muh. Irvan Nur'iva; Rahayu Rahayu; Herman H (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
This study analyzes the transformation of public governance from the New Public Management (NPM) paradigm to Digital-Era Governance (DEG) through the implementation of the Electronic-Based Government System (SPBE) in Indonesia. Employing a descriptive-analytical qualitative approach, this research utilizes secondary data from policy documents and academic literature, which is analyzed via an interactive model. The findings reveal that SPBE marks a fundamental shift from the fragmented NPM to an integrated (joined-up government), citizen-centric, and data-driven DEG paradigm. Although Indonesia has established a strong regulatory foundation synergized with the One Data Indonesia initiative, empirical implementation remains hindered by cultural and structural challenges. These include digital literacy gaps among state apparatus, sectoral egos hindering system interoperability, cybersecurity vulnerabilities, and infrastructure inequalities in 3T (frontier, outermost, and underdeveloped) regions. In conclusion, public bureaucracies must evolve into adaptive learning organizations. Overcoming these obstacles requires strong digital leadership, enhanced digital culture, accelerated interoperability, and equitable infrastructure distribution. Keywords: Digital-Era Governance; Digital Leadership; Digital Transformation; Electronic-Based Government System (SPBE); New Public Management